Peer evaluation tournaments - Martin Dufwenberg; Katja Görlitz; Christina Gravert (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2024)
Peer evaluation tournaments are common in academia, the arts, and corporate environments. They make use of the expert knowledge that academics or team members have in assessing their peers' performance. However, rampant opportunities for cheating may throw a wrench in the process unless, somehow, players have a preference for honest reporting. Building on Dufwenberg and Dufwenberg's (2018) theory of perceived cheating aversion, we develop a multi-player model in which players balance the utility of winning against the disutility of being identified as a cheater. We derive a set of predictions, and test these in a controlled laboratory experiment.
Keywords: C91; 330; psychological game; cheating; tournaments; laboratory experiment